Intronic polyadenylation–derived long noncoding RNA modulates nucleolar integrity and function - Sumana Mallick; Pranita Borkar; Jaspreet Thind; Daniel Chung; Taylor Hubbs; Irtisha Singh (Proceedings of the National Academy of Sciences, 2026)
RNAs transcribed from protein-coding gene loci are widely assumed to be translated into proteins. However, intronic polyadenylation (IPA) occurring near the transcription start site or within early introns can generate noncoding RNAs derived from protein-coding loci. Despite their abundance, the functional roles of such RNAs remain largely unexplored. In this study, we investigated one such noncoding RNA, CUL1-IPA , transcribed from the CUL1 gene locus. Our study revealed that CUL1-IPA is an RNA polymerase II–dependent IPA isoform that is polyadenylated, stable, and translocates to the nucleolus. Functional characterization demonstrated CUL1-IPA to play a critical role in maintaining nucleolar integrity. RNA-protein interaction assay identified GPATCH4 and NOP58, nucleolar proteins involved in ribosomal RNA (rRNA) processing, as binding partners of CUL1-IPA . Consistent with its localization and interactions, loss of CUL1-IPA led to the reduction in rRNA levels and consequent decrease in overall protein synthesis. This effect on rRNA levels could be reversed by reintroducing CUL1-IPA , confirming its functional importance. Furthermore, as nucleolar stress is known to affect cell cycle progression, we found that CUL1-IPA loss resulted in G2/M cell cycle phase arrest. Moreover, reduced CUL1-IPA expression was associated with improved survival outcomes in cancer patients. Together, our findings demonstrate that CUL1-IPA , an IPA-derived long noncoding RNA (lncRNA), forms an RNA-protein complex in the nucleolus to support nucleolar structure and function. This study provides an insight into the biological function of a lncRNA originating from a protein-coding gene and highlights the broader significance of IPA-derived noncoding RNAs as regulatory molecules.